# Solve for p q=160-5/2p q=160-52p
Rewrite the equation as 160-52p=q.
160-52p=q
Simplify each term.
Combine p and 52.
160-p⋅52=q
Move 5 to the left of p.
160-5p2=q
160-5p2=q
Subtract 160 from both sides of the equation.
-5p2=q-160
Multiply both sides of the equation by -25.
-25⋅(-5p2)=-25⋅(q-160)
Simplify both sides of the equation.
Simplify -25⋅(-5p2).
Cancel the common factor of 2.
Move the leading negative in -25 into the numerator.
-25⋅(-5p2)=-25⋅(q-160)
Move the leading negative in -5p2 into the numerator.
-25⋅-5p2=-25⋅(q-160)
Factor 2 out of -2.
2(-1)5⋅-5p2=-25⋅(q-160)
Cancel the common factor.
2⋅-15⋅-5p2=-25⋅(q-160)
Rewrite the expression.
-15⋅(-5p)=-25⋅(q-160)
-15⋅(-5p)=-25⋅(q-160)
Cancel the common factor of 5.
Factor 5 out of -5p.
-15⋅(5(-p))=-25⋅(q-160)
Cancel the common factor.
-15⋅(5(-p))=-25⋅(q-160)
Rewrite the expression.
-1⋅(-p)=-25⋅(q-160)
-1⋅(-p)=-25⋅(q-160)
Multiply.
Multiply -1 by -1.
1⋅p=-25⋅(q-160)
Multiply p by 1.
p=-25⋅(q-160)
p=-25⋅(q-160)
p=-25⋅(q-160)
Simplify -25⋅(q-160).
Simplify terms.
Apply the distributive property.
p=-25q-25⋅-160
Combine q and 25.
p=-q⋅25-25⋅-160
Cancel the common factor of 5.
Move the leading negative in -25 into the numerator.
p=-q⋅25+-25⋅-160
Factor 5 out of -160.
p=-q⋅25+-25⋅(5(-32))
Cancel the common factor.
p=-q⋅25+-25⋅(5⋅-32)
Rewrite the expression.
p=-q⋅25-2⋅-32
p=-q⋅25-2⋅-32
Multiply -2 by -32.
p=-q⋅25+64
p=-q⋅25+64
Move 2 to the left of q.
p=-2q5+64
p=-2q5+64
p=-2q5+64
Solve for p q=160-5/2p

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top